Membangun Karakter Peserta Didik Sekolah Dasar melalui program 7 Poe Atikan (nyucikeun diri). - Nurfadilah, Arini; Fajriana, Firda Rahma; Ridho Wardani, Muhammad Rosyad; Wahyudin, Dede; Caturiasari, Jennyta (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
Purwakarta Regency is one of the regions in West Java that remains focused on restoring local wisdom in its community, one of which is the promotion of the special 7 Poe Atikan Purwakarta program in Purwakarta. Strengthening the implementation of character education in Purwakarta Regency includes several functions of training and mentoring students both inside and outside school according to the level of elementary school education, improving themselves who are empowered, have a strong mentality, spiritual, have good morals and have the skills they need for themselves, both in the community and at school. This research uses a qualitative descriptive approach and the method used is a literature review. Â Based on the content of the 7 Special Atikan Poe program implemented in Purwakarta area schools, it is very desirable because judging from the content of activities that take place from Monday to Friday it can foster good habits of students so that their character will be formed. become. It also appears, shaping the character of religion, mutual aid, nationalism, integration, and independence that the nation awaits